1997
DOI: 10.1097/00007632-199701010-00011
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study Comparing the Oswestry and Roland-Morris Functional Disability Scales in Two Populations of Patients With Low Back Pain of Different Levels of Severity

Abstract: The authors conclude that both functional disability scales accurately discriminated between these two groups of patients with low back pain of very different clinical and electromyographic severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 14 publications
5
72
0
2
Order By: Relevance
“…Convergent validity was examined by investigating the strength of the relationship between the ODI and various other indices of disability (RM score and Likert scale ratings) and LBP intensity. The ODI showed a somewhat higher correlation with the RM (r=0.80) than has been previously reported {r=0.66 (LBP patients with radicular pain), r=0.72 (low back sprain) [30]; r=0.73 [10]}. However, it was noticed that extrapolation of the regression equation for the relationship between ODI and RM, to a maximum RM score (24 points), yielded an ODI score of just 70 points.…”
Section: Construct Validity Of the Odimentioning
confidence: 53%
See 1 more Smart Citation
“…Convergent validity was examined by investigating the strength of the relationship between the ODI and various other indices of disability (RM score and Likert scale ratings) and LBP intensity. The ODI showed a somewhat higher correlation with the RM (r=0.80) than has been previously reported {r=0.66 (LBP patients with radicular pain), r=0.72 (low back sprain) [30]; r=0.73 [10]}. However, it was noticed that extrapolation of the regression equation for the relationship between ODI and RM, to a maximum RM score (24 points), yielded an ODI score of just 70 points.…”
Section: Construct Validity Of the Odimentioning
confidence: 53%
“…The number and nature of both the items and their response categories differ between the two questionnaires, but their purpose is generally the same; namely to indicate the extent to which a person's activities of daily living are disrupted or restricted by low-back pain (LBP). It has been suggested that the RM may be better suited to settings in which patients have mild to moderate disability and the ODI to situations in which patients may have persistent severe disability [34], although studies in which the two questionnaires have been directly compared in a range of patient types are actually rare [30,37].…”
mentioning
confidence: 99%
“…Repeated measurements performed on the same day and at 3 weeks are highly correlated [9,16,22,28]. The RolandMorris scale has good criterion-based construct and discriminant validity and is the most responsive disability questionnaire for back pain currently available [3,9,10,16,18,22,[27][28][29]. Raw scores, recorded on an integer scale ranging from 0 (no disability) to 24 (severe disability), are transformed into percentages.…”
Section: Functional Limitationsmentioning
confidence: 99%
“…This self-rating scale evaluates the degree of functional impairment caused by pain in activities of daily living [30,31,32].…”
Section: Minnesota Multiphasic Personality Inventory (Mmpi-2)mentioning
confidence: 99%